Advances in molecular adjuvants for nucleic acid vaccines - Hojecki, Casey E.; Tursi, Nicholas J.; Livingston, Cory; Weiner, David B.; Gary, Ebony N. (Frontiers in Immunology, 2025)
As nucleic acid vaccine technology continues to advance, modern adjuvants are being engineered to quantitatively and qualitatively shape immune responses. Since their development in the early 1990’s, nucleic acid approaches have garnered significant attention, and numerous platform technologies have been developed both to improve delivery as well as immunogenicity. These advances were highlighted during the COVID-19 pandemic, with the approval of both mRNA-LNP and DNA vaccines for SARS-CoV-2. Early clinical trials with DNA antigens alone displayed suboptimal immunogenicity, supporting interest in adjuvant molecules. Molecular adjuvants, nucleic acid-encoded cytokines, chemokines, and enzymes, among others, are used to enhance and direct nucleic acid antigen-induced immunity in vivo. Additionally, mRNA-LNP vaccines, and more recently DNA-LNP vaccines, have demonstrated robust immunogenicity with intrinsic adjuvant activity based on the delivery mode. This review summarizes the molecular adjuvant landscape and highlights recent findings in the context of nucleic acid vaccines.